Skills assessment report (draft) (The Project GeorgetownGY, 2002)
Delineates the major areas of focus and the structure and responsibilities of the Caricom Secretariat's sixteen work-programmes. Provides a summary assessment of the staff resources functioning in the programmes and the experience and skills deemed imperative to effective project execution. Presents the skills of UWI personnel pertinent to the programme areas and identifies areas for CARICOM/UWI collaboration.
Additional copy located in the Office of the Secretary-General